Is Management a Science? - Gribbins, Ronald E.; Hunt, Shelby D. (Academy of Management Review, 1978)
The article discusses the concept of management science and compares scientific method to management phenomena. An argument is developed in which practices in the discipline of management fulfill the criteria that defines science—such as having a specific subject matter that is based in the real world, the presumption of underlying relationships in the phenomena being studied, and the application of inter-subjectively certifiable methods of studying a distinct subject matter—and therefore management should be recognized as a science.